MODEL LITERASI MEDIA SOSIAL BAGI MAHASISWA - Muhammad Sulthan; S Bekti Istiyanto (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2019)
The development of internet communication technology today is unstoppable, especially for students. Many negative impacts have arisen in the use of social media due to wrong use. This study aims to find a social media literacy model for unsoed Purwokerto students. The researcher used a qualitative approach with in-depth interviews, focus group discussions and literature studies as data collection techniques. The subjects of this study were Unsoed Social Sciences Department students who actively use social media every day. The results of the study found a social media literacy model for Unsoed students based on the media literacy model proposed by Potter. Students use social media according to the needs and peculiarities of existing social media, both from exchanging information and maintaining friendships to the reasons for the process of learning, economics, entertainment, and self-actualization; students know of any negative impacts and irregularities that occur due to inappropriate use of social media. However, they still use social media. Such because it is already a demand in everyday life.